Soft skills profile of critical thinking ability for culinary arts students in online learning - Kokom Komariah; Siti Hamidah; Sugiyono Sugiyono; Kurni Marifa (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
The ability to think critically has become a demand in the 21st century. This paper describes how culinary arts students' soft skills ownership profile after participating in online learning through the communication media application used. This study is survey research, processed by quantitative description. The research subjects were the culinary arts study program students with diploma 4 and bachelor's degrees, Department of Food and Clothing Engineering, Faculty of Engineering, Universitas Negeri Yogyakarta. The population of this study is all students who are part of ongoing online learning. Samples were taken at simple random. The data collection technique used a questionnaire via google form; the goal was affordability from the aspect of place and time. The study focuses on mastering soft skills in learning and innovation skills, especially critical thinking and problem-solving. The survey results show that Catering lecturers widely use online media, such as the Google Meet application, Google Classroom, and Be-Smart. More than half of the soft skills profiles displayed by culinary arts students show critical thinking behaviors (61%). The behavior of critical thinking soft skills that is quite prominent is the ability to think rationally, consider well to solve problems and be able to make creative solutions to tasks found during learning. Online learning implies that it is necessary to increase human resources, especially lecturers, in optimizing online media applications. Students need support in the form of triggers and the preparation of learning tools that can awaken critical thinking skills.